Simulation to Implementation as Good Practices for Teaching Power Electronics to Undergraduate Students: Fuzzy Sliding Mode Control for DC Motors. (24th February 2014) - Cepeda, Paul; Ponce, Pedro; Molina, Arturo
Abstract : How can students be given experience in the confused realities of engineering processes? How can undergraduate students be convinced that processes can be analyzed and improved? Computer simulations properly designed and applied could answer these challenges revolutionizing education in Power Electronics. In recent years, computer simulation has been commonly used in education to motivate students in their learning and help teachers to improve their teaching level. The present paper focuses on developing a speed controller for DC motors starting from theoretical aspects, passing through simulations, and finally reaching a control prototype. The control theory is based on a nonlinear technique known as Sliding Mode Control (SMC) involving artificial intelligence for optimization such as Fuzzy Logic (FL), Adaptive Neurofuzzy Inference Systems (ANFIS), and Genetic Algorithms (GAs).